Audience Response of Working Women in Hidden Figures Movie 2016 - Dwi Puspita Sari; Zainuddin Zainuddin (Universitas Negeri Medan, 2022)
This study is about audience response of working women in Hidden Figures Movie which is aimed to reveal the response of the audience about working women in Hidden Figures Movie. This study used the reader-response theory by Rosenblatt (1982). Data were analyzed by using interpretative qualitative method. the interview sheet is used as the instrument to find out the valid data. The study showed varied responses toward the working women in Hidden Figures Movie. The response of the audience is classified into two categories; positive and negative. The finding of this study showed that all the audience response is a positive response. It shows that all the response is support the women who work and having a career. There are the difference between female response and male response toward working women in Hidden Figures Movie where male audience believed that there should be a limitation for married women to work. The difference also shows that the opinion is came from different brain, and absolutely with different thought.